Review of heterobranch molluscs fauna in the Boka Kotorska Bay, Montenegro - Jovanović, Milica (Array, 2019)
Heterobranch molluscs fauna in Montenegro has been poorly investigated so far. The aim of the present paper is to improve the knowledge about species diversity of these marine organisms in the Boka Kotorska Bay, specific fjord-like entity in the southern Adriatic Sea. New records of seven heterobranch species were obtained by field surveys in 2017, while three new records were provided by analysing underwater photographs from previous periods. The resulted checklist summarizes the knowledge of the diversity of heterobranchs in the Boka Kotorska Bay from the oldest record in 1967 to the present day and consists of a total of 62 heterobranch species.